(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Basti is one of the most important Panchakarma used in the treatment of various disorders. It is a method of administrating the medicine in the form of Kwatha or Sneha in the body through anal region or urinary or vaginal route. Basti in which Sneha is used for administration is known as Anuvasana Basti. Vata is the major cause in manifestation of diseases affecting the Shakha, Koshtha and Marma. Anuvasana Basti can be used a single therapy for various Vataja Vikaras. This can also be used as Purva Karma before Niruha Basti as well as Paschata Karma after Niruha Basti. Ancient Acharyas have mentioned the details of Anuvasana Basti in accordance with useful Dravyas, its indications, contraindications, Basti Vidhi, complications, importance, etc., Samhitakaras have also mentioned the different Yogas along with their specific indications. An attempt has been made here to review the concept of Anuvasana Basti in Brihattaryi and to study the different Yogas of Anuvasana Basti as mentioned in them.